Structures in Tetrahydrofolate Methylation in Desulfitobacterial Glycine Betaine Metabolism at Atomic Resolution. (18th November 2019) - Badmann, Thomas; Groll, Michael
Abstract: Enzymes orchestrating methylation between tetrahydrofolate (THF) and cobalamin (Cbl) are abundant among all domains of life. During energy production in Desulfitobacterium hafniense, MtgA catalyzes the methyl transfer from methylcobalamin (Cbl‐CH3 ) to THF in the catabolism of glycine betaine (GB). Despite its lack of sequence identity with known structures, we could show that MtgA forms a homodimeric complex of two TIM barrels. Atomic crystallographic insights into the interplay of MtgA with THF as well as analysis of a trapped reaction intermediate (THF‐CH3 ) + reveal conformational rearrangements during the transfer reaction. Whereas residues for THF methylation are conserved, the binding mode for the THF glutamyl‐ p ‐aminobenzoate moiety (THF tail) is unique. Apart from snapshots of individual reaction steps of MtgA, structure‐based mutagenesis combined with enzymatic activity assays allowed a mechanistic description of the methyl transfer between Cbl‐CH3 and THF. Altogether, the THF‐tail‐binding motion observed in MtgA is unique compared to other THF methyltransferases and therefore contributes to the general understanding of THF‐mediated methyl transfer. Abstract : Enzyme catalysis in action : In the glycine betaine metabolism of D. hafniense, MtgA catalyzes methyl transfer from methylcobalamin to tetrahydrofolate (THF). Using protein X‐ray crystallography combined with mutagenesis and enzymatic activity assays, we were able to obtain mechanistic insights into this regioselective methylation. Structural snapshots of MtgA during catalysis reveal discrepancies towards other THF methyltransferases.